Catalytic hydrogenation of N-4-nitrophenyl nicotinamide in a micro-packed bed reactor. Issue 4 (30th January 2018) - Yang, Cuixian; Teixeira, Andrew R.; Shi, Yanxiang; Born, Stephen C.; Lin, Hongkun; Li Song, Yunfei; Martin, Benjamin; Schenkel, Berthold; Peer Lachegurabi, Maryam; Jensen, Klavs F.
Abstract : Recent advancements in micro-flow technologies and a drive toward more efficient, greener and safer processes have led to a renaissance in flow-chemistry for pharmaceutical production. Abstract : Recent advancements in micro-flow technologies and a drive toward more efficient, greener and safer processes have led to a renaissance in flow-chemistry for pharmaceutical production. In this work, we demonstrate the use of a stabilized Pd nanoparticle-organic-silica catalyst to selectively catalyze the hydrogenation of N -4-nitrophenyl nicotinamide, a functionalized active pharmaceutical ingredient (API) surrogate. Extensive catalyst and reactor characterization is provided to establish an in-depth understanding of the unique multiphase dynamics within the micro-packed bed reactor, including the identification of a large liquid holdup (74–84%), rapid multiphase mass transfer ( k m a > 1 s −1 ), and liquid residence time distributions. A kinetic analysis has revealed that the surface catalyzed hydrogenation progresses through a condensation mechanism whereby an azo dimer intermediate is formed and rapidly consumed. Finally, a parametric study was performed at various pressures, temperatures, residence times and flow regimes to achieve quantitative chemoselective conversion of the nitroarene to the corresponding primary amine.